Near-infrared thermally activated delayed fluorescence of D–π-A–π-D difluoroboron complex for efficient singlet oxygen generation in aqueous media. Issue 16 (11th July 2022) - Li, Ziyong; Yang, Xiao-Gang; Zhang, Haining; Zhang, Ji-Rui; Tian, Xu-Ke; Qin, Jian-Huan; Ma, Lu-Fang; Yan, Dongpeng
Abstract : NIR TADF difluoroboron complex shows extremely small Δ E ST, broad absorption range (350–650 nm), high 1 O2 quantum yield (62%), and selective photodynamic killing of Gram-positive bacteria. Abstract : The rational design of novel photosensitizers with broad absorption and small singlet–triplet energy gap (Δ E ST ) is of great importance for photodynamic therapy and photocatalytic reactions. Herein, a new type of thermally activated delayed fluorescence (TADF) material, BCzSFB, was designed and synthesized by the bonding of superior electron acceptor difluoroboron β-diketonate, electron donor carbazole and π-bridged styrene. The D–π-A–π-D structure of BCzSFB ranges at the nanoscale (with a length of about 2.4 nm), showing extremely small Δ E ST (0.08 eV), broad absorption range (350–650 nm), and long lifetime of NIR TADF even as nanoparticles dispersed in aqueous media. It presents high singlet oxygen ( 1 O2 ) quantum yield (62%, higher than that of state-of-the-art dyes and commercial methylene blue and eosin blue), and selective photodynamic killing of Gram-positive bacteria. Nearly 100% of S. aureus can be killed in 10 minutes at a low white light dose (60 mW cm −2 ).